2018
DOI: 10.1029/2018gl079968
|View full text |Cite
|
Sign up to set email alerts
|

234Th‐Derived Particle Fluxes and Seasonal Variability: When Is the SS Assumption Reliable? Insights From a Novel Approach for Carbon Flux Simulation

Abstract: 234Th measurements are widely used to estimate the downward carbon flux of particles via the oceanic Biological Pump. Carbon export is evaluated from 234Th‐238U disequilibrium assuming either steady state (SS) conditions, or including a non‐SS (NSS) correction. We use a novel stochastic simulation to quantify the temporal variation of vertical carbon and 234Th (dissolved and particulate) concentration profiles with high temporal resolution. We calculate seasonal export as if in situ measured with sediment trap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…These estimates do not, however, provide information about the nature of the particles responsible for the measured fluxes, and rely on assumptions regarding the conversion from radioisotopes to carbon that are difficult to evaluate (Waite and Hill, 2006). Moreover, radioisotopic estimates of particle flux are complicated by potential non-steady state dynamics and physical transport (Ceballos-Romero et al, 2018). Measurements are costly, as they need to be conducted during individual oceanographic cruises, and need to be calibrated with sediment traps.…”
Section: Autonomous Sampling On the Risementioning
confidence: 99%
“…These estimates do not, however, provide information about the nature of the particles responsible for the measured fluxes, and rely on assumptions regarding the conversion from radioisotopes to carbon that are difficult to evaluate (Waite and Hill, 2006). Moreover, radioisotopic estimates of particle flux are complicated by potential non-steady state dynamics and physical transport (Ceballos-Romero et al, 2018). Measurements are costly, as they need to be conducted during individual oceanographic cruises, and need to be calibrated with sediment traps.…”
Section: Autonomous Sampling On the Risementioning
confidence: 99%
“…The data are archived on PANGAEA repository, with the dataset's DOI https://doi.pangaea.de/10.1594/PANGAEA.918125 (Ceballos-Romero et al, 2021). The data table is available for download either as a unique merged file containing all data sets and metadata or as individual excels files.…”
Section: Data Formats and Availabilitymentioning
confidence: 99%
“…More than 41% of the studies reported POC: 234 Th ratios collected with sediment traps (Haskell et al, 2013;Kawakami et al, 2010;Luo et al, 2014;Maiti et al, 2016). Almost all the studies of the studies reported measurements CHN data (88%), while a very reduced number (~10%) analyzed 210Po (such as Alkalay et al, 2020 and only 3 studies simultaneous measured and discussed 234 Th-derived results from 234 Th, 210Po and compared then to fluxes from sediment traps (Ceballos-Romero et al, 2016;Le Moigne et al, 2013a;and Stewart et al, 2010). Overturning (UK, https://roses.ac.uk/piccolo/).…”
Section: Era 4: "20000 Legs Under the Sea"mentioning
confidence: 99%
See 2 more Smart Citations